KEBIJAKAN DIVIDEN, HUTANG, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Pery Sutisna; Jaja Suteja (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2020)
Firm value was a goal that must be achieved in the context of the welfare of shareholders. The objective of this research was to investigate the effect of dividend policy, debt policy, and profitability to firm value of property and real estate industries in 2012-2016. Population of this research was property and real estate companies listed in Indonesia Stock Exchange (IDX). The sampling method used was purposive sampling and the results were 10 companies according to the criteria of the sample. Method analysis using pooled regression. The results showed that dividend policy, debt policy, and profitability have significant effect to firm value simultaneously. Partially, dividend and debt policy have not significant effect to the firm value partially, but profitability has significant effect.